Baby Death Due to Esophagotracheal Fistula Created by An Alkaline Battery: A Case Report - Teke, Hacer Yaşar; Can, Muhammet; Renklidağ, Tülay; Temel, Nevriye; Gökmen, Asude (The Bulletin of Legal Medicine, 2018)
There is a limited number of case presentations in literature related to esophagus burns and complications as a result of swallowing an alkaline battery. The main purpose of this case presentation was to discuss the autopsy findings of late-developing complications of swallowing an alkali battery in the light of the relevant literature.On the chest radiography of a 9-month old baby with complaints of vomiting for three days, an opacity was observed consistent with a foreign body in the esophagus. Esophagoscopy was applied and the swallowed battery was removed. On the fifth day after the operation, no complication has been observed to oral feeding was started and on the following day the patient was discharged. Four days after discharge, the patient was again brought to hospital with complaints of blood in vomit and was again hospitalized with a diagnosis of chemical esophageal burn. The patient died on the following day....
Keywords: alkaline battery; esophagotracheal fistula; autopsy; forensic medicine